Knowledge of perianal Crohn's disease among nurses in an Italian tertiary centre. (2nd November 2022) - Napolitano, Daniele; Cioffi, Federica; Marocchini, Giannina; Bernabei, Tiziana; Leonetti, Alessia; Fanali, Caterina; Orgiana, Nicoletta; Amatucci, Valeria; Gasbarrini, Antonio; Ratto, Carlo; Litta, Francesco; Scaldaferri, Franco
Abstract : Background: Patients with Crohn's disease can develop anal and perianal lesions, such as fistulas, ulcers, skin tags, perianal abscesses and strictures. Perianal Crohn's disease (PCD) is a condition that has a major impact on patients' quality of life. The multidisciplinary team includes a nurse who manages the patient according to evidence-based medicine. Clinical practice and post-registration training are the way forward for nurses to acquire the skills needed to deliver quality care. Aims: This study explored the assessment of nurses' knowledge of PCD. A cross-sectional survey was used to look at the nurses' knowledge. Methods: The questionnaire was administered over 2 months, between September and October 2019. The questionnaire was anonymous, validated by a panel of experts in the field and consisted of 30 questions to assess knowledge and two questions to assess the need for training. It was directed to 120 clinical nurses in the departments of medicine and abdominal surgery. Results: There were 120 nurses enrolled, and 64.2% of nurses had cared for patients with PCD at least once. The survey showed a fairly low level of knowledge of the diagnostic and therapeutic care pathways for patients affected by PCD. On the other hand, a high need for training and in-depth study of the subject emerged. Conclusion: The nurse, an integral part of the multidisciplinary team, plays an important role in the education of these patients. Nurses' present level of knowledge can certainly be improved thanks to their willingness to undertake training courses or to use information tools.